Spontaneous theory of mind in autism: are anticipatory gaze and reaction time biases consistent? - Onda, Keigo; Ichwansyah, Rizal; Kawasaki, Keisuke; Egawa, Jun; Someya, Toshiyuki; Hasegawa, Isao (Frontiers in Psychiatry, 2024)
BackgroundIndividuals with autism spectrum disorder (ASD) exhibit persistent deficits in social interaction and communication in adulthood. Pioneering studies have suggested that these difficulties arise from a lack of immediate, spontaneous mentalizing (i.e., theory of mind: ToM), specifically, an ability to attribute false beliefs to others, which should be usually acquired during neurotypical development. However, this view has been challenged by recent reports of nonreplications of spontaneous mentalizing, even in neurotypical adults.ObjectivesWe aimed to evaluate (1) whether measurements of spontaneous ToM in two representative paradigms, gaze bias in the anticipatory looking (AL) test and reaction time bias in the object detection (OD) test, are correlated in neurotypical adults and (2) whether these two measurements are altered in individuals with ASD.MethodsWe developed a novel hybridized spontaneous false belief test combining the AL and OD paradigms to enable within-subject comparison of different spontaneous ToM measurements.ResultsThe results obtained with our hybridized test replicated the earlier positive evidence for spontaneous ToM in both AL and OD paradigms. Our results also revealed a correlation between the participants’ spontaneous gaze bias in the AL paradigm and reaction time bias in the OD paradigm, indicating that the participants who had spontaneously anticipated other’s false belief driven actions more quickly detected the object. We further found that spontaneous gaze and reaction time biases were altered in individuals with ASD. Finally, we ascertained those inclusions of these biases as diagnostic variables in a regression model improved the accuracy of diagnosing ASD. ASD diagnosis was best predicted by the model when variables obtained from both AL and OD methods were included in the model.Conclusions/implicationsOur hybridized paradigm not only replicated spontaneous gaze bias in early AL studies and reaction time bias in the OD paradigms, but indicated significant correlation between them, suggesting that different implicit tasks tap the same spontaneous ToM in neurotypical adults. Group differences of these indices between ASD and neurotypical adult groups indicated that our task could help diagnose ASD, which is essential for evaluating the social difficulties that individuals with ASD face in adulthood.